New rules on the protection of consumer credit users - Mićović, Andrej (BizInfo Blace, 2025)
The article analyzes the rules cotained in the EU Directive 2023/2225 on consumer credit agreements, which in comparison to the previous ones (contained in Directive 87/102, which was modified by Directives 90/88 and 98/7, and Directive 2008/48), are significant step forward towards creating the conditions for achieving long-established goals: a high level of consumer protection and the development of a single credit market. These rules refer to those that regulate for the first time some issues related to the advertising of credit agreements and consumer information, rules that determine the position of creditors and consumers regarding the provision of certain services, rules on the conduct of business obligations of creditors (credit intermediaries), as well as rules on restrictive and educational measures for the purpose of consumer protection.
Keywords: consumer; creditor; protection; service